2018
DOI: 10.1371/journal.pone.0197704
|View full text |Cite
|
Sign up to set email alerts
|

Data-assisted reduced-order modeling of extreme events in complex dynamical systems

Abstract: The prediction of extreme events, from avalanches and droughts to tsunamis and epidemics, depends on the formulation and analysis of relevant, complex dynamical systems. Such dynamical systems are characterized by high intrinsic dimensionality with extreme events having the form of rare transitions that are several standard deviations away from the mean. Such systems are not amenable to classical order-reduction methods through projection of the governing equations due to the large intrinsic dimensionality of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
118
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 215 publications
(119 citation statements)
references
References 57 publications
1
118
0
Order By: Relevance
“…With the growing interest in data-driven modeling of ROMs using machine learning (ML) architectures, there has been another dimension of research introduced to the community for the improvement in ROM performance, referred as hybrid ROM approach. Generally, the hybridization is done by combining an imperfect physics-based model with a data-driven technique to get a hybrid scheme, and it is observed that the hybrid model shows better predictive performance than the component models [52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…With the growing interest in data-driven modeling of ROMs using machine learning (ML) architectures, there has been another dimension of research introduced to the community for the improvement in ROM performance, referred as hybrid ROM approach. Generally, the hybridization is done by combining an imperfect physics-based model with a data-driven technique to get a hybrid scheme, and it is observed that the hybrid model shows better predictive performance than the component models [52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…However, the literature on applications of ML to dynamical instabilities is remarkably scarce. The only related investigation of which we are aware was conducted by Wan et al 31 , who used long-short-term-memory neural networks to predict occurrences of extreme events in chaotic systems.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, for example for large-scale, multi-physics, multi-scale dynamical systems such as weather and climate models, it is likely that a hybrid framework yields the best performance: depending on the application and the spatio-temporal scales of the physical processes involved [18,76], some of the equations could be solved numerically with double precision, some could be solved numerically with lower precisions, and some could be approximated with a surrogate model learned via data-driven approach. Such inexact data-assisted frameworks enable integrating the known physics and PDEs with the AI models, thus overcoming the challenges arising from shortness of datasets, poorly understood physics, and partially known PDEs [77,54], while allowing for automated tuning to make the best use of the computing power and resources. As mentioned before, the data-driven models (e.g., a neural network) can be also designed to benefit from the concepts and philosophy of inexact computing (i.e., reduce precision, save resources, reinvest wisely).…”
Section: Discussionmentioning
confidence: 99%